EVALUASI PEMBERIAN TERAPI NSAID PADA PASIEN OSTEOARTHRITIS DI POLI RAWAT JALAN RS WISMA PRASHANTI - Indra Marangyana, I Gede Bagus; Sindhu Aditama, I Gede Agus; Widiani, Ni Putu Astuti (Institut Teknologi dan Kesehatan Bintang Persada, 2024)
The prevalence of osteoarthritis in Indonesia has reached quite high numbers¾5% at the age of 40 years, 30% at the age of 40-60 years, and 65% of elderly people over 61 years. Osteoarthritis occurs more often in women than men. Osteoarthritis management is recommended in certain conditions using Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). NSAIDs have various side effects such as obstruction, impaired kidney function, cardiovascular disorders, gastrointestinal disorders. Therefore, it is necessary to evaluate the use of NSAIDs regarding appropriate indications, drug selection and dosage. This study aims to determine the profile of use and evaluate the rationality of NSAID prescribing. This type of research is descriptive observational. Data collection was carried out retrospectively using medical records at Wisma Prasanthi Hospital. The subjects of this study were outpatients in the period July-December 2023 and met the inclusion criteria. The results of the study showed that the highest use of NSAIDs was the non-selective group (100%), i.e. Diclofenac Sodium (48.71%), Meloxicam (23.07%), Ibuprofen (19.23%), Caltrofen (7.69%), and Topical NSAID is Diclofenac gel (1.28%). The rationality of prescribing oral and topical NSAIDs is 100% right indication, 100% right drug selection, and 100% right dose. The conclusion from this study is that the highest use of NSAIDs is the non-selective NSAID group and the rationality for correct indications, correct drug selection and correct dosage is 100%.